Disposition of methylmercury over time in a 75% nephrectomized rat model. Issue 10 (19th May 2018) - Orr, Sarah E.; Joshee, Lucy; Barkin, Jennifer; Bridges, Christy C.
ABSTRACT: Chronic kidney disease (CKD) is a highly relevant clinical condition that is characterized by the permanent loss of functional nephrons. Individuals with CKD may exhibit impaired renal clearance, which may alter corporal handling of metabolites and xenobiotics. Methylmercury (MeHg) is an important environmental toxicant to which humans are exposed to on a regular basis. Given the prevalence of CKD and ubiquitous presence of MeHg in the environment, it is important to understand how mercuric ions are handled in patients with CKD. Therefore, the purpose of the current study was to characterize the disposition of MeHg over time in a rat model of CKD (i.e., 75% nephrectomized (NPX) rats). Control and NPX rats were exposed intravenously (iv) to a non-nephrotoxic dose of MeHg (5 mg/kg) once daily for1, 2, or 3 d and the amount of MeHg in organs, blood, urine, and feces determined. The accumulation of MeHg in kidneys and blood of controls was significantly greater than that of NPX animals. In contrast, MeHg levels in brain and liver of controls were not markedly different from corresponding NPX rats. In all organs examined, accumulation of MeHg increased over the course of exposure, suggesting that urinary and fecal elimination are not sufficient to fully eliminate all mercuric ions. The current findings are important in that the disposition of mercuric ions in rats with normal renal function versus renal insufficiency following exposure to MeHg for a prolonged period differ and need to be taken into account with respect to therapeutic management.